Covalent functionalization of MXenes for tribological purposes - a critical review - Parra-Muñoz, Nicole; Soler, Monica; Rosenkranz, Andreas (Advances in colloid and interface science, 2022)
Transition metal carbides, nitrides and carbonitrides (MXenes) have recently attracted notable attention in tribology and, particularly solid lubrication, due to their low shear strength and ability to form low-friction, wear-resistant tribo-layers. Their use as lubricant additives has only shown limited success due to their inherent hydrophilic character, causing a low phase-compatibility and dispersion-stability with pure base oils. To overcome this shortcoming and to boost MXenes' tribological performance as lubricant additive and reinforcement phase in composites, their tuneable surface chemistry moves into the focus of current research. Originating from chemical etching to synthesize MXenes, their outer surface contains a variety of surface terminations, which can function as anchoring points for molecules via covalent grafting/functionalization. By adopting an adequate functionalization strategy, this, in turn, can help to tailor MXenes' hydrophobicity, dispersion stability, restacking tendency, or oxidation resistance. This directly affects their dispersion stability in base oils and improves their phase compatibility with other matrix materials in composites, thus resulting in an enhanced tribological performance. Therefore, this review concisely summarizes the existing state-of-the-art regarding MXenes' covalent functionalization with a particular emphasis on tribological properties and needs, a topic, which has not been holistically reviewed yet. The first chapter sheds light on the existing synthesis approaches with detailed insights regarding the resulting surface terminations, which are crucial for the subsequent chemical functionalization. After summarizing strategies to increase their interlayer distance to improve the accessibility for chemical functionalization and the existing state-of-the art regarding MXene tribology, we critically discuss the existing functionalization strategies using different coupling agents (organosilanes, organophosphorus agents, aryldiazonium agents, among others). Subsequently, we emphasize on the crucial role of homogeneously distributed -OH surface terminations to guarantee the overall success of the functionalization approach and to boost the resulting tribological performance. Lastly, we address the existing challenges and derive future research directions. We anticipate that our article can serve as an excellent guide for MXenes' chemical functionalization, which can be useful in various applications including tribology thus paving the way towards enhanced physical and chemical properties of MXenes.Transition metal carbides, nitrides and carbonitrides (MXenes) have recently attracted notable attention in tribology and, particularly solid lubrication, due to their low shear strength and ability to form low-friction, wear-resistant tribo-layers. Their use as lubricant additives has only shown limited success due to their inherent hydrophilic character, causing a low phase-compatibility and dispersion-stability with pure base oils. To overcome this shortcoming and to boost MXenes' tribological performance as lubricant additive and reinforcement phase in composites, their tuneable surface chemistry moves into the focus of current research. Originating from chemical etching to synthesize MXenes, their outer surface contains a variety of surface terminations, which can function as anchoring points for molecules via covalent grafting/functionalization. By adopting an adequate functionalization strategy, this, in turn, can help to tailor MXenes' hydrophobicity, dispersion stability, restacking tendency, or oxidation resistance. This directly affects their dispersion stability in base oils and improves their phase compatibility with other matrix materials in composites, thus resulting in an enhanced tribological performance. Therefore, this review concisely summarizes the existing state-of-the-art regarding MXenes' covalent functionalization with a particular emphasis on tribological properties and needs, a topic, which has not been holistically reviewed yet. The first chapter sheds light on the existing synthesis approaches with detailed insights regarding the resulting surface terminations, which are crucial for the subsequent chemical functionalization. After summarizing strategies to increase their interlayer distance to improve the accessibility for chemical functionalization and the existing state-of-the art regarding MXene tribology, we critically discuss the existing functionalization strategies using different coupling agents (organosilanes, organophosphorus agents, aryldiazonium agents, among others). Subsequently, we emphasize on the crucial role of homogeneously distributed -OH surface terminations to guarantee the overall success of the functionalization approach and to boost the resulting tribological performance. Lastly, we address the existing challenges and derive future research directions. We anticipate that our article can serve as an excellent guide for MXenes' chemical functionalization, which can be useful in various applications including tribology thus paving the way towards enhanced physical and chemical properties of MXenes.